Direct medical costs in the treatment of hypertension and diabetes comorbidity at Thong Nhat Dong Nai General Hospital in 2024 - Hang, Nguyen Thuy; Thang, Do Huynh Quoc; Linh, Pham Thi Thuy; Thuy, Nguyen Thi Thu; Y, Nguyen Tran Nhu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Comorbidity of hypertension and diabetes mellitus (HTN - DM) is becoming increasingly prevalent, leading to growing cost burden. Objective: To analyze direct medical costs (DMCs) in the treatment of HTN - DM comorbidity at Thong Nhat Dong Nai General Hospital in 2024. Methods: A cross-sectional descriptive study based on retrospective electronic billing data of patients at Thong Nhat Dong Nai General Hospital in 2024 was conducted. All cases that met the inclusion criteria and did not violate the exclusion criteria during the data collection period were included. Results: A total of 50,800 treatment episodes with the mean age of 66.7 ± 10.2 years and the female-to-male ratio of 1.4:1 recorded the mean DMC for HTN - DM comorbidity of 679,843 VND (95%CI: 669,503 - 690,182 VND) per outpatient episode and 11,389,334 VND (95%CI: 10,780,602 - 11,998,065 VND) per inpatient episode. Medication costs accounted for the largest proportion of outpatient expenses (63.4%), whereas medical supplies accounted for the highest share in inpatient care (29.1%); health insurance payments covered most of the total DMCs for both outpatient and inpatient episodes (88.1% and 84.4%, respectively). Factors associated with both outpatient DMCs and inpatient DMCs included gender, type of insurance coverage, insurance reimbursement rate, area of residence, primary diagnosis, reason for visit, number of comorbidities, dyslipidemia, treatment outcomes, and discharge status. Additionally, age and comorbid ischemic heart disease were associated with outpatient DMCs, while length of hospital stay were associated with inpatient DMCs. Conclusion: DMCs for the treatment of HTN - DM comorbidity are considerably high, equivalent to 0.1 times the average monthly per-capita income per outpatient visit and 2.1 times per inpatient episode. Inpatient episodes with a primary diagnosis of ischemic heart disease and comorbid dyslipidemia incurred substantial DMCs; therefore, strengthening strategies for the effective clinical management and control for these conditions is warranted to reduce the economic burden.